2010
DOI: 10.1111/j.1478-3231.2010.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy increases hepatic triglyceride content and very‐low‐density lipoproteins production in mice

Abstract: XGB increased serum and hepatic TG levels, and VLDL production, which were restored to normal by nicotinic acid. The results suggest that FFA flux from adipose tissue to the liver is increased in XGB mice. They support the hypothesis that the GB has a role in the regulation of hepatic TG metabolism and that XGB may favour the accumulation of fat in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 77 publications
3
49
2
5
Order By: Relevance
“…Sonne et al ( 33 ) recently demonstrated a slight deterioration of postprandial glycemic control aft er GB removal, and even an increase in body weight has been reported in cholecystectomized patients ( 34 ). Moreover, and in line with current data from Ruhl and Everhard, recent studies in cholecystectomized mice have shown an increase in hepatic and serum TGs concentration, very-low-density lipoprotein synthesis and production, and BA pool cycling ( 35 ).…”
mentioning
confidence: 76%
“…Sonne et al ( 33 ) recently demonstrated a slight deterioration of postprandial glycemic control aft er GB removal, and even an increase in body weight has been reported in cholecystectomized patients ( 34 ). Moreover, and in line with current data from Ruhl and Everhard, recent studies in cholecystectomized mice have shown an increase in hepatic and serum TGs concentration, very-low-density lipoprotein synthesis and production, and BA pool cycling ( 35 ).…”
mentioning
confidence: 76%
“…Following surgery, the size of the BA pool remains within a normal range and dietary fat absorption remains unaffected. 4,5 However, there is emerging evidence showing that cholecystectomy itself may lead to an excessive risk for the surgical patient developing metabolic disorders and their associated complications, including dyslipidemia, nonalcoholic fatty liver disease (NAFLD), and hyperglycemia. [5][6][7] The unexplained high incidence of these metabolic abnormalities among cholecystectomized patients, combined with the lack of data regarding metabolic changes that occur after GB removal, has caused cholecystectomies to receive increased scrutiny.…”
mentioning
confidence: 99%
“…4,5 However, there is emerging evidence showing that cholecystectomy itself may lead to an excessive risk for the surgical patient developing metabolic disorders and their associated complications, including dyslipidemia, nonalcoholic fatty liver disease (NAFLD), and hyperglycemia. [5][6][7] The unexplained high incidence of these metabolic abnormalities among cholecystectomized patients, combined with the lack of data regarding metabolic changes that occur after GB removal, has caused cholecystectomies to receive increased scrutiny. As the roles of the GB and BAs in systemic metabolic regulation have become better understood, [8][9][10] it is important to re-examine the potential long-term negative outcomes of GB removal, and especially the associated risk for subsequent metabolic syndrome (MetS).…”
mentioning
confidence: 99%
“…In sham-operated control mice, the peritoneal cavity was opened and exposed, but the cystic duct was neither ligated nor removed [32] . After ensuring that the mice continued to gain weight nor-mally, we orally administered DHP107 to the sham-operated and cholecystectomized mice at a dose of 50 mg/kg under fasted conditions (n=5/time point).…”
Section: Cholecystectomy and Sampling In Micementioning
confidence: 99%